Homeopathy and Psychotherapy: Clarifications on Differences and Similarities. A Comparative Analysis of Related but Distinct Disciplines - De Giorgio, Giovanni; Tarro, Giulio (British Journal of Healthcare and Medical Research, 2026)
Homeopathy is a medical discipline based on the law of similarity and treats patients through the administration of diluted and dynamized substances, while psychotherapy is a therapy based on the word, etymologically meaning "cure of the soul." The two disciplines have similarities and differences, so this article provides clarifications to distinguish them and foster an interdisciplinary dialogue based on conceptual order and scientific rigor.